Chia seed mucilage – a vegan thickener: isolation, tailoring viscoelasticity and rehydration. Issue 8 (22nd July 2019) - Brütsch, Linda; Stringer, Fiona J.; Kuster, Simon; Windhab, Erich J.; Fischer, Peter
Abstract : Chia seeds and their mucilage gels provide a nutritionally and functionally promising ingredient for the food and pharmaceutical industry. Abstract : Chia seeds and their mucilage gels provide a nutritionally and functionally promising ingredient for the food and pharmaceutical industry. Application and utilization of the gel remain limited due to the tightly adhesion of the mucilage to the seeds, which affects the organoleptic properties, control of concentration and structuring possibilities. To exploit the full potential of chia mucilage gels as a functional ingredient calls for separation and purification of the gel. Herein, the gel was extracted by centrifugation and characterized rheologically and microscopically to link the viscoelastic properties to the structural properties. Subsequently, the gel was dried employing three different methods for facilitated storage and prolonged shelf life. The dried gels were readily soluble and its viscoelastic properties were fully regenerated upon rehydration demonstrating its potential to envisage industrial applications. The viscoelastic chia mucilage demonstrated shear-thinning behavior with complete relaxation upon stress removal. The gel's elasticity was enhanced with increasing mucilage concentration resulting in a highly tunable system. The extractable and rehydratable functional chia gel is a viable candidate as additive for the development of products requiring specific viscoelastic properties. Addition of the gel enhances the nutritional profile without interfering with the organoleptic properties.